2004
DOI: 10.1080/00071660400006552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of different surface decontaminants on chicken quality

Abstract: (1) A comparative study on the effect of different surface decontaminants: hot water at 70 degrees C for one minute; 2% lactic acid for 30 s; 1200 p.p.m. acidified sodium chlorite (ASC) solution for 5 s and 50 p.p.m. chlorine solution for 5 min in the form of dips and sprays on the surface of dressed broilers for 0, 24 and 48 h of storage was conducted. (2) The variables studied were, total plate count (TPC), presumptive coliform count (PCC), pH and extract release volume (ERV). All treatments reduced TPC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
5
21
0
1
Order By: Relevance
“…It is in agreement with Sinhamahapatra et al, (2004) and Jay et al, (2003). It was found that mean ERV value showed highly significant difference on 3 rd , 5 th and 6 th day in between three treatments.…”
Section: Erv (Extract Release Volume)supporting
confidence: 78%
“…It is in agreement with Sinhamahapatra et al, (2004) and Jay et al, (2003). It was found that mean ERV value showed highly significant difference on 3 rd , 5 th and 6 th day in between three treatments.…”
Section: Erv (Extract Release Volume)supporting
confidence: 78%
“…Zeitoun and Debevere (1992) and Pipek et al (1997) used spraying alone whereas Sakhare et al (1999) recommended dipping or spraying, based on finding a 0.9 log 10 cfu cm À2 reduction in aerobic plate counts using dipping after evisceration, and a 1.0 log 10 cfu cm À2 reduction using spraying. After 0, 24 and 48 h of storage, Sinhamahapatra et al (2004) found that reductions in aerobic plate counts were 0.2e0.3 log 10 cm À2 less after spraying compared to immersion. Okolocha and Ellerbroek (2005) also concluded that dipping gave the best overall reductions; however, their results table shows that, on the day of treatment, spraying 1 L of solution, spraying 2 L of solution, or dipping, produced microbial reductions of 0.4, 1.3, or 0.6 log 10 cfu per millilitre of carcass rinse, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…A literature survey of decontamination treatments for poultry by Loretz, Stephan, and Zweifel (2010) identified just two studies (Sakhare, Sachindra, Tashoda, and Narasimha Rao (1999), Sinhamahapatra, Biswas, Das, and Bhattacharya (2004)) where the effect on the aerobic plate counts of spraying lactic acid on naturally contaminated carcasses at slaughter, or soon after, was examined. Both studies reported a reduction in aerobic bacteria of 1e1.1 log 10 cfu cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine disinfection has been extensively applied in the harvest and postharvest handling of fresh fruits and vegetables for many decades because it is effective, chemically stable, readily available, relatively inexpensive, and easily applied. For example, chlorine has been routinely used for disinfection of vegetables such as lettuce, carrots, and spinach (12,20,21), fruits such as strawberries, apples, cantaloupe, honeydew melons, and tomatoes (22)(23)(24)(25)(26), chicken (27), and fish (28). A recent progress in chlorine disinfection is the generation of chlorine water through electrolysis (29,30).…”
Section: Introductionmentioning
confidence: 99%